Система тестового контролю метрологічних характеристик технологічного процесу - Кондрашов, Сергій Іванович; Мигущенко, Руслан Павлович; Опришкіна, Марина Ігорівна; Мацак, Ольга Владиславівна (НТУ "ХПІ", 2015)
У роботі розглянуті актуальні питання підвищення точності первинних вимірювальних перетворювачів з нелінійною дробово-раціональною функцією перетворення. Розроблена система тестового контролю метрологічних характеристик вимірювальних каналів дозволила підвищити якість продукції та заощадити технічні і матеріальні ресурси. Підвищення точності ємнісного каналу вимірювання у автоматичній ливарній машині після застосування системи становить 15%. Впровадження системи дозволило контролювати стан первинних перетворювачів без переривання технологічного процесу.

The paper discusses the current issues of improving the accuracy of transducers with non-linear rational function transformation. To solve this problem we apply the theoretical developments in the field of test control. The algorithm of the test product testing. The developed system test control of metrological characteristics of measuring channels can improve product quality and save the technical and material resources. Increasing the accuracy of capacitive measurement channel in an automatic casting machine after the introduction of the system is 15%. Using the system will monitor the status of primary transducers without interrupting the process. Control of metal level has enhanced productivity and product quality.
System test control metrological characteristics of the process
Keywords: давач ємнісний; модель реляційно-різницева; перетворювач вимірювальний; capacitive sensor; relational-difference model